Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Bmt Amanah Ummah Kabupaten Sukoharjo - Santoso, Herry; , Lukman Hakim, S.E., M.Si (2016)
Interest in the study are: (1) To determine the factors of service quality (tangibles, reliability, responsiveness, assurance, empathy) partially and simultaneously influence on customer satisfaction BMT Amanah Ummah Sukoharjo district. (2) To determine the factors that influence the quality of service of the most dominant on customer satisfaction BMT Amanah Ummah Sukoharjo district. This research is a survey. The population is all customers BMT Amanah Ummah Sukoharjo district. Sample of 100 respondents with convenience sampling technique. The data analysis method used: (1) Test Instruments Research, namely Test Validity and Test Reliability, (2) Classical Assumption Test, ie Normality Test, Test Multicolinearity and Test Heteroskidastity, (3) Hypothesis, namely Test Regression Test, t , Test F and Test coefficient of Determination. The results of data analysis showed that: (1) Test Instruments Research, all declared valid and reliable questionnaire. (2) Classical Assumption Test, no error occurs in the classical assumptions. (3) Test the hypothesis, the results obtained: (a) individual t test showed physical evidence, reliability, responsiveness, assurance and concern a significant effect on customer satisfaction. (B) Test F shows together physical evidence, reliability, responsiveness, assurance and concern a significant effect on customer satisfaction. (C) Multiple Linear Regression Testing concern variable is the variable that most large standardized coefficient, these results suggest that the variables of concern is the variable that most affect customer satisfaction. (D) Test Coefficient of Determination R2 has a value large enough, these results demonstrate the quality of service is able to explain the variable large enough customer satisfaction. Keywords: Quality of care (physical form, reliability, responsiveness, assurance, awareness), customer satisfaction